Candidate-centric systems and the politicization of ethnicity: evidence from Indonesia. Issue 7 (3rd October 2018) - Fox, Colm
ABSTRACT: When and why do electoral candidates politicize ethnicity? From the literature, we might expect this behaviour to occur during democratic transitions or under proportional rules. However, empirical support for these arguments is mixed. This article presents a new approach, arguing that candidate-centric rules offer candidates incentives to politicize ethnicity. The argument is tested in Indonesia with empirical evidence drawn from coding newspaper reports on campaign events, endorsements and group appeals. Indonesia used party-centric rules from 1997 to 2004, and even though the country democratized during this period, the politicization of ethnicity actually declined. I show how party-centric rules, coupled with a national economic crisis, encouraged candidates to campaign on broad national platforms of reform and development, thereby appealing to the poor rather than to ethnic groups. Between 2004 and 2009, the system became more candidate-centric and the politicization of ethnicity increased. I argue that changes in the system freed candidates from national party platforms and motivated them to campaign on their local connections with ethnic groups. This study is particularly pertinent amidst the push for direct candidate-centric elections in the developing world and the lack of literature on how such rules could affect ethnic politics.